Coronavirus-related health literacy levels among school administrators and influencing factors - Ozturk, Fatma Ozlem; Sonmez, Sibel; Soylar, Pinar; Okan, Orkan; Dadaczynski, Kevin (Oxford Univ Press, 2023)
Our study aimed to determine the level of coronavirus-related health literacy among school administrators and the factors that influence this. The sample of this cross-sectional study consisted of 402 school administrators serving in primary, secondary and high schools in Ankara. The data were collected between September 2021 and February 2022 using the descriptive characteristics questionnaire and the Coronavirus-Related Health Literacy Questionnaire (HLS-COVID-Q22). It was seen that 64.4% of the participants were male, 34.6% were 40 years old or younger and 35.6% were working in primary schools; 77.6% of the participants had a sufficient, 16.2% had a problematic and 6.2% had an inadequate level of coronavirus-related health literacy. Age, gender, chronic disease status, type of school they work in, level of knowledge about coronavirus, level of confusion due to knowledge about coronavirus, willingness to be vaccinated, believing that vaccines are safe/effective/compatible with their religious beliefs were found to affect coronavirus-related health literacy (p < 0.05). Gender, age, information satisfaction on coronavirus, confusion due to information on coronavirus and 'Overall, I believe that vaccinations are effective' explained 24.9% of HLS-COVID-Q22 variance (Adjusted R-2 = 0.249, F = 13.080, p < 0.001). This study found the coronavirus-related health literacy level among school administrators to be sufficient. It found that their level of health literacy was affected by gender, age, chronic disease status, type of school they worked at, level of knowledge about coronavirus, level of confusion due to information about coronavirus, desire to be vaccinated and their thoughts about vaccines.
Keywords: health literacy; COVID-19 pandemic; vaccines; health promotion schools; health promotion